Substructure and orientation heterogeneity of polycrystalline aluminum and its changes during plastic deformation - Badiyan, E.E.; Tonkopryad, A.G.; Shekhovtsov, O.V.; Shurinov, R.V.; Zetova, T.R. (Functional Materials, 2016)
The results of experimental studies of the regularities of subgrain structure changing during plastic deformation of large-grained aluminum specimens with a parquet structure are presented. For most of the grains it is shown that the main substructure change has been the fragmentation of the subgrain structure, which is accompanied by an increase in the spectral width of misorientations. The effect of a dispersal of grain boundaries has been found and the mechanism of such dispersal is defined. The mechanism of the rotation of individual grains during deformation of the specimen and the subgrain structure role in such rotation are investigated. It is shown in experiment that specific and consistent restructuring of the subgrain structure took place in the individual grains during deformation of the specimen. It led to a change in crystallographic orientation of the grain, on the one hand, and to the relative deformation of the grain, which was significantly higher than the relative deformation of the entire specimen, on the other hand. Fine block structure with a wide spectrum of misorientations which changed during deformation of the grain was found near the boundaries of such grains. The presence of such a structure near grain boundaries played an accommodative role and excluded the possibility of discontinuities in grain and grain boundaries during deformation of the specimen.